2006
DOI: 10.4028/www.scientific.net/msf.532-533.1032
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Method for Product Material Selection Considering Environmental Factors and a Case Study

Abstract: Materials have very important influence on the environmental impact of the product life cycle from production to disposal and recycling. The environmental factors should be considered when product materials are selected, in order to improve the environmental friendliness of products. Due to the complexity of product material selection considering technical, economic and environmental factors, it is transformed into a decision-making problem. An integrated decision-making index system is presented, and a multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…[107][108][109][110][111] showed that GRA's effectiveness consisted of nonlinear constraints, uncertainties, and conflicting objectives condition. With uncertainties in evaluating, Cao et al 108 and Chan and Tong 111 considered environmental GRA when selecting a material. However, integrations suggested by non-linear constraints and uncertainties from sustainable and green materials present subjectivity and conflicting evaluation criteria.…”
Section: Optimisation and Mathematical Methodsmentioning
confidence: 99%
“…[107][108][109][110][111] showed that GRA's effectiveness consisted of nonlinear constraints, uncertainties, and conflicting objectives condition. With uncertainties in evaluating, Cao et al 108 and Chan and Tong 111 considered environmental GRA when selecting a material. However, integrations suggested by non-linear constraints and uncertainties from sustainable and green materials present subjectivity and conflicting evaluation criteria.…”
Section: Optimisation and Mathematical Methodsmentioning
confidence: 99%
“…al., 2010) 1-Machine tool (Antonio et. al., 2012) 1-Printer (Boonkanit and Apikajornsin, 2005) 2-Wheelchair (Hambali, 2008) 3-Automotive (Hambali, 2008) 4-Hospital Bed (Sarfaaz and Jenab, 2012) 1-Electronic housing (Cao et. al., 2006) 2-Key (Dweiri and Oqla, 2009) 3-Automotive (Mayyas et.…”
Section: Manufacturing Processmentioning
confidence: 99%
“…They compared their findings with the multiplicative competitive interaction model and found that the grey approach yielded the better solution. Cao et al [29] developed an integrated grey decision model for the selection of the material of a product.…”
Section: Introductionmentioning
confidence: 99%
“…Most methods for supplier selection are analytic hierarchy processes [1,3,4], which depend on subjective data provided by experts. In [25][26][27][28][29], grey incidence analysis with equal weighting has been used for supplier selection, as it does not require large or regular data samples and hence has an important practical significance. However, their methods require subjective data from experts and equally weighted factors and initial data to form behavioural sequences are needed to calculate the degree of grey incidence in Deng's grey incidence analysis.…”
Section: Introductionmentioning
confidence: 99%